IMPACT OF THE GREAT PERTAINING TO SCHOOL GAMES IN THE MARKET OF WORK OF THE PROFESSIONAL OF PHYSICAL EDUCATION IN SERGIPE (Fiep Bulletin - online, 2012)
The Hegemony with in the Schoolof Sporthas recently beena central themewith in the Physical Education, an issue thattendsto intensifywiththe approach ofmajorworld sporting eventsto beheld in Brazilin the comingyears.It isintended towork, to establish a historical relationship between sportsandschooland their relationshipon thelabor market of thephysical education professional.Understand thissocial phenomenonand interfere withthe way it operateswithin the Schoolisvery important forthe teacher of physical education, regardless of their educational visionorphilosophical alignment.This studyis descriptive in nature.We usedasemi-structured questionnaireappliedrandomly andfor convenience,where theintervieweespresentedtheir viewson thesubject of proposed study.The final sample included43teachers andsportscoordinators,who workedinphysical education,during the period1990to the present day.Importantis still clearly seethe direct relationshipbetween sports,and more specifically,between the implementation of majorschool eventsandwork of this professionalmarket,thismarketin constantchange and transformation, a source ofanguish and anxietyof modern man,who hastheworkyourown corporate identity.
Keywords: SportGames; School; Work